2012
DOI: 10.2147/ijn.s29690
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of VEGF mRNA expression by triamcinolone acetonide acetate-loaded chitosan derivative nanoparticles in human retinal pigment epithelial cells

Abstract: Background:The purpose of this study was to investigate the downregulation of mRNA expression of vascular endothelial growth factor (VEGF) by triamcinolone acetonide acetate (TAA)-loaded chitosan nanoparticles in human retinal pigment epithelial cells. Methods: TAA-loaded deoxycholic acid-modified chitosan (TAA/DA-Chit) nanoparticles were prepared via a self-assembly mechanism, and their morphology and zeta potential were examined by transmission electron microscopy and zeta potential analysis, respectively. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Given the apparent role of inflammation in the pathogenesis of DR and DME, intravitreal steroids have been utilized for the treatment of DME. The mode of action is unclear, but it has been suggested to be through multiple mechanisms including their ability to inhibit expression of VEGF [ 146 , 147 ]. The effects of steroids on microglia under DR and DME conditions remain unknown; however, other ocular disease models are starting to elucidate the effects of intravitreal corticosteroid delivery on microglia.…”
Section: The Effects Of Diabetes Treatments On Microgliamentioning
confidence: 99%
“…Given the apparent role of inflammation in the pathogenesis of DR and DME, intravitreal steroids have been utilized for the treatment of DME. The mode of action is unclear, but it has been suggested to be through multiple mechanisms including their ability to inhibit expression of VEGF [ 146 , 147 ]. The effects of steroids on microglia under DR and DME conditions remain unknown; however, other ocular disease models are starting to elucidate the effects of intravitreal corticosteroid delivery on microglia.…”
Section: The Effects Of Diabetes Treatments On Microgliamentioning
confidence: 99%
“…While in-depth toxicity studies will be conducted in future, we observe no histological or functional signs of gross retinal toxicity or degeneration following subretinal delivery of GCS NPs. This is particularly important as unmodified chitosan in the eye has been shown to induce some toxic effects [28] (although other modified chitosans, such as deoxycholic acid-substituted chitosan were shown not be cytotoxic [29] ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the conjugated nanochitosan peptide showed evidence of tyrosine kinase activity as indicated by fluorescent signals under the confocal microscope, while nanochitosan or peptide alone did not show such activity. Zhou et al ( 42 ) designed a study for investigating the downregulation of mRNA expression of VEGF by triamcinolone acetonide acetate (TAA)-loaded chitosan nanoparticles in human retinal pigment epithelial cells. The study demonstrated that TAA/loaded deoxycholic acid (DA)-modified chitosan nanoparticles had a downregulating effect on VEGF mRNA expression in human retinal pigment epithelial cells with low cytotoxicity; these are beneficial characteristics suggesting the suitability of these chitosan-derived nanoparticles to be developed into therapeutics for diabetic retinopathy.…”
Section: Current Status Of Gene Therapy Of Ocular Diseasementioning
confidence: 99%